Sapatero in Marikina City enacting economies in the Philippines footwear capital - Rapisora, Ma. Concepcion B.
"This study argues that Marikina city's nostalgically popular trademark as the Philippines' footwear capital has been made possible by sapatero in the past and present who have enacted a localised economy.